Tax Incentive Policy for Micro, Small and Medium Enterprises (UMKM) Affected by the Covid-19 Pandemic Related with Utility Principle - Sundary, Rini Irianti; Effendy, Deddy; Sukmamulya, Liya; Berliana, erlyn; Yulistia, Intan (KnE Social Sciences, 2023)
Taxes serve both budgetary and non-budgetary functions. The non-budgetary function entails regulation and addressing financial challenges. With the global impact of the Covid-19 pandemic since late 2019, various sectors are required to contribute and play a role, including the taxation sector fulfilling its regulatory function. This research adopts a normative juridical approach, relying on secondary data with descriptive analytical specifications. The tax incentives implemented by the government aim to support the industrial sector and its related components during the pandemic. However, the long-term implications of tax incentive policies may prove unfavorable for the community. On one hand, tax cuts can stimulate an increase in household consumption expenditure. The findings of this study reveal that the Indonesian government has taken commendable measures to protect its citizens and the national economy amidst the Covid-19 outbreak. Alongside monetary policy, fiscal policy stands as one of the government’s primary tools in addressing the economic downturn caused by the pandemic. Keywords: intensive, tax, policy, Covid-19